Experimental investigation of heat transfer coefficient of mini-channel PCHE (printed circuit heat exchanger). (June 2018) - Kwon, Dohoon; Jin, Lingxue; Jung, WooSeok; Jeong, Sangkwon
Highlights: Thermal performance of a mini-channel PCHE under cryogenic condition is studied. Single-phase, boiling and condensation experiments are conducted. Empirical heat transfer correlations are proposed at each experimental condition. Abstract: Heat transfer coefficient of a mini-channel printed circuit heat exchanger (PCHE) with counter-flow configuration is investigated. The PCHE used in the experiments is two layered (10 channels per layer) and has the hydraulic diameter of 1.83 mm. Experiments are conducted under various cryogenic heat transfer conditions: single-phase, boiling and condensation heat transfer. Heat transfer coefficients of each experiments are presented and compared with established correlations. In the case of the single-phase experiment, empiricial correlation of modified Dittus-Boelter correlation was proposed, which predicts the experimental results with 5% error at Reynolds number range from 8500 to 17, 000. In the case of the boiling experiment, film boiling phenomenon occurred dominantly due to large temperature difference between the hot side and the cold side fluids. Empirical correlation is proposed which predicts experimental results with 20% error at Reynolds number range from 2100 to 2500. In the case of the condensation experiment, empirical correlation of modified Akers correlation was proposed, which predicts experimental results with 10% error at Reynolds number range from 3100 to 6200.